Intranasal odorant concentrations in relation to sniff behavior. - Beauchamp, Jonathan; Scheibe, Mandy; Hummel, Thomas; Büttner, Andrea (Chemistry & Biodiversity, 2014)
Knowledge on how odorants are transported through the nasal cavity to the olfactory epithelium is limited. One facet of this is how the sniffing behavior affects the abundance of odorants transferred to the olfactory cleft and in turn influences odor perception. A novel system that couples an online mass spectrometer with an odorant pulse delivery olfactometer was employed to characterize intranasal odorant concentrations of butane-2,3-dione (or butanedione, commonly known as diacetyl) at the interior naris and the olfactory cleft. Volunteers (n=12) were asked to perform different modes of sniffing in relation to the sniff intensity that were categorized as 'normal', 'rapid' and 'forced'. The highest concentrations of butanedione at both positions in the nose were observed during normal sniffing, with the lowest concentrations correlating with periods of forced sniffs. This corresponded to the panelists' ratings that normal sniffing elicited the highest odor intensities. These feasibility assessments pave the way for more in-depth analyses with a variety of odorants of different chemical classes at various intranasal positions, to investigate the passage and uptake of odorants within the nasal cavity.<br